THE EFFECT OF AQUATIC THERAPY AT DIFFERENT LEVELS OF WATER DEPTH ON FUNCTIONAL BALANCE AND WALKING CAPACITY IN CHILDREN WITH CEREBRAL PALSY: Life Science-Pathology - FATOREHCHY, SAEID; ALI HOSSEINI, SEYED; RASSAFIANI, MEHDI (International Journal of Life Science and Pharma Research, 2019)
The purpose of this study was to evaluate the effects of aquatic therapy program on functional balance and walking capacity in children with cerebral palsy. The sample consisted of six children (4 boys and 2 girls) with cerebral palsy. The average age of the participants was 7 year 4 months ± 1y 2mo (Mean ±SD). All the children were able to walk independently with or without assistive devices. Gross Motor Function Classification System levels of the participants were I to III. This scale divides walking ability into 5 levels. The aquatic program lasted for 8 weeks and twice per week. Each session lasted for 50 minutes, comprising 10 minutes of warm-up and stretching and 40 minutes of walking in the pool at different levels of water depth. Each child started walking at nipple height water every five minutes the depth of water was decreased by 1 inch. Functional balance (pediatric balance scale) and walking capacity (1minute walk test) were evaluated before and after intervention. Changes in functional balance were statistically significant between initial and final testing, at p= 0.026. There was statistically significant change in the walking capacity, between initial and final testing, at p= 0.041.Functional balance and walking capacity were improved in children with cerebral palsy following aquatic therapy in the pool at different levels of water depth.